Disruption of TBC1D7, a subunit of the TSC1-TSC2 protein complex, in intellectual disability and megalencephaly. Issue 11 (17th May 2013) - Capo-Chichi, José-Mario; Tcherkezian, Joseph; Hamdan, Fadi F; Décarie, Jean Claude; Dobrzeniecka, Sylvia; Patry, Lysanne; Nadon, Marc-Antoine; Mucha, Bettina E; Major, Philippe; Shevell, Michael; Bencheikh, Bouchra Ouled Amar; Joober, Ridha; et al.
Abstract : Background: Mutations in TSC1 or TSC2 cause the tuberous sclerosis complex (TSC), a disorder characterised by the development of hamartomas or benign tumours in various organs as well as the variable presence of epilepsy, intellectual disability (ID) and autism. TSC1, TSC2 and the recently described protein TBC1D7 form a complex that inhibits mTORC1 signalling and limits cell growth. Although it has been proposed that mutations in TBC1D7 might also cause TSC, loss of its function has not yet been documented in humans. Methods and Results: We used homozygosity mapping and exome sequencing to study a consanguineous family with ID and megalencephaly but without any specific features of TSC. We identified only one rare coding variant, c.538delT:p.Y180fsX1 in TBC1D7, in the regions of homozygosity shared by the affected siblings. We show that this mutation abolishes TBC1D7 expression and is associated with increased mTORC1 signalling in cells of the affected individuals. Conclusions: Our study suggests that disruption of TBC1D7 causes ID but without the other typical features found in TSC. Although megalencephaly is not commonly observed in TSC, it has been associated with mTORC1 activation. Our observation thus reinforces the relationship between this pathway and the development of megalencephaly.